PUBLIC TRANSPORTATION SYSTEM FARE, ECONOMIC IMPACTS ON THE PURCHASING POWER OF ITS USERS, THE CASE OF BOGOTÁ, COLOMBIA - German PRIETO-RODRIGUEZ; Olmer GARCIA-BEDOYA (Scientific Journal of Silesian University of Technology. Series Transport)
The public transportation fare in a city is an important determinant of accessibility, equity, and quality of life for its citizens. This article makes a comparative quantitative analysis of the fare of the public transportation system in the city of Bogotá (Colombia), its evolution over time, and the impact on the poorest users. It compares with similar systems in Latin America and other cities in the world. The findings show that the fare has had high growth in US dollars (USD 0.38 in 2000 to 0.75 in 2024), but the purchasing capacity has increased with respect to the local minimum wage (10.84 tickets with a minimum daily wage, versus 14.69 in 2024). This rate is one of the highest in Latin America and has a high impact on lower-income citizens, since the purchase of 50 monthly tickets is equivalent to 15% of the local monthly minimum wage.